The Influence and Strategy of Ar-Rum Financing as Marketing in Improving Customer Micro Business at PT. Pegadaian Syariah Unit Kejuruan Muda - Khilda Amalia (Yayasan Adra Karima Hubbi, 2024)
Background. PT. Pegadaian Syariah offers Arrum Financing products as a solution to help micro business actors get additional business capital. This product is expected to help the development of micro businesses, especially with the support of effective marketing strategies. Increasing micro businesses is one of the main goals in providing easy access to capital and in accordance with sharia principles, which is expected to have an impact on the growth of Sharia Pawnshop customers. Purpose. This study aims to analyze the influence of Arrum financing and marketing strategies on the increase of micro business customers in PT. Sharia Pawnshops of Young Business Units, both partially and simultaneously. Method. This study used a quantitative method involving 86 respondents. Data collection is carried out through questionnaires, observations, and documentation. The collected data was analyzed using SPSS version 25 software. The statistical tests carried out include partial tests (t-test) and simultaneous tests (F-test) to assess the influence of each variable. Results. The results of the study show that partially, Arrum Financing has a significant influence on the increase in customer micro businesses with a significance value of 0.000 < ? 0.01. In addition, marketing strategy also has a significant influence on the increase in micro businesses with a significance value of 0.000 < ? 0.01. Simultaneously, Arrum financing and marketing strategy, based on the F test, showed a significant influence on the increase in micro enterprises with a significance value of 0.000. Conclusion. Arrum financing and marketing strategies partially and simultaneously have a significant influence on the increase in customer micro businesses in PT. Sharia Pawnshop. This shows that both financing and marketing strategies play an important role in supporting the development of micro businesses in the institution.